The Effect of Product Quality and Price on Purchase Decisions through Customer Satisfaction at the Marketplace Shopee (Case Study on Employees of PT Wahana Makmur Sejati) - Muhammad Ardiyansyah; Helena Louise P (Budapest International Research and Critics Institute-Journal (BIRCI-Journal), 2022)
This research is a result of capturing the quality of the product weight and cost satisfaction. This research channel is based on PT Wahana Makmur which uses the shopee marketplace. This research uses quantitative method where the technique of unification of questionnaire data. So that the sample quantity of 112 respondents. Data is worked on SPSS software version 25. Data analysis techniques use path analysis. The indirect harvesting of product quality through Customer Satisfaction has positive and significant effect on the Purchase Decision, and also Price through Customer Satisfaction has positive and significant effect on the Purchase Decision. In equation 1, Product Quality has a significant influence on Customer Satisfaction, while Price also has a significant influence on Customer Satisfaction. For equation 2 states that Product Quality has a significant influence on Purchasing Decisions, Price has a significant influence on Purchasing Decisions, and Customer Satisfaction also has a significant influence on Purchasing Decisions. Thus it can be concluded that Product Quality and Price simultaneously have a significant effect on Customer Satisfaction, while Product Quality, Price and Customer Satisfaction simultaneously have a significant effect on Purchasing Decisions.